Fundamentals of Entrepreneurship (ENT300) : Cecaro Departy'Lo Cafe / Jc Recho Japial... [et al.] - Japial, Jc Recho; William, Fabian; Luli, Ehlid; Hesamuddin, Sabaruddin; Amir, Siti Nur Syafiqah (2011)
This business is based on partnership where it consists of five members. The members consist of the General Executive, Administrative Executive, Marketing Executive, Operational Executive and Financial Executive. All of these positions play crucial roles and altogether are accountable to the establishment and operation of this company with the aim to run the business effectively and to attain the maximum profit. We believe that with the less competition and big support from the customers' demands towards this business, we can successfully achieve the goals that have stated in this business plan. This business is based on partnership where it consists of five alleys. The alleys consist of the General Executive, Administrative Executive, Marketing Executive, Operational Executive and Financial Executive. All of these positions play crucial roles and altogether are accountable to the establishment and operation of this company with the aim to run the business effectively and to attain the maximum profit. We believe that with the less competition and big support from the customers' demands towards this business, we can successfully achieve the goals that have stated in this business plan